Minat Beli Kaum Milenial Pengguna Instagram - Selfia Ratna Kasih; Asep M. Ramdan; Acep Samsudin (Program Studi Manajemen Fakultas Ekonomi UST, 2020)
The purpose from this reaserch is for measuring how much the influence of social media like instagram and confidence of customers so millennial interest to buy. Variabel of this research is media social instagram (x1), consumer trust (x2), and purchase intention millennials (y), methods that used in this research is quantitative methods with associative approach, with sharing questioner by online as much 359 to millennials who have productive age. There also analysis. Goals from analysis test showing media social instagram and consumer trust has significant effect to purchase intention millennials and goals of mediation hypothesis test showing that variable consumer trust mediating social media instagram to purchase intention millenial.